Reinforcing Interventions on Child Abuse for Social Work Practitioners - Yuka, Vivian Aliemeke; Omorogiuwa, Tracy B.E. (NIU Journal of Social Sciences, 2026)
There has been a global call for reinforcing interventions on child abuse for social work practitioners, where children are exposed to situations that impedes on their well-being. Specifically, the study investigated the prevalence of child abuse, and it interrogated social work intervention strategies in combating child abuse in Egor Local Government Area in Edo State, Nigeria. The study adopted the quantitative and qualitative research methods, where the cross-sectional research design was adopted in collecting quantitative data. The study covered selected public secondary schools, and target participants were children within the age range of 11-17years which were both male and female, who are secondary school students, parents/guardians’, teachers and social workers. A sample size of 400 respondents was adopted, and the research instrument for collecting data were the questionnaire and in-depth interview guide. The findings identified a prevailing trend that children suffered considerable emotional, psychological, and physical distress as a result of abuse. It also revealed a broad agreement in affirming that social work interventions could positively influence the health of abused children. Lack of awareness about children's rights allows the cycle of abuse to continue. Majority of the respondents who had experienced abuse were not supported enough. The study recommended the need to strengthening reporting mechanisms, education on children’s rights, collaboration with law enforcement and legal system. Keywords: child, abuse, social work, interventions, reinforce, children, Advocacy, practitioners